The The Effect of Nutrition Education Using Videos and E-booklets on Increasing Knowledge of Balanced Nutrition in High School Students in Jakarta - Rachmi Ilma Zahtira; Nur Intania Sofianita (Ikatan Sarjana Gizi Indonesia (ISAGI), 2022)
Abstract: The adolescent counts as a productive age group who needs an adequate nutritional intake to ensure their productivity in their studies and work. A long-term period of unbalanced nutrition consumption might impact one's health and productivity. One of the interventions that can be done is through education to increase their knowledge of balanced nutrition. The media used in this research are e-booklets and videos. Objectives: This research aims to understand the difference between balanced nutrition knowledge before and after nutritional education using E-booklets and videos among high school students in Jakarta and also to find the difference in the effectiveness of both media. Methods: The sampling technique used in this research was random sampling with a total of 95 respondents. The method used is a quasi-experiment with a Wilcoxon test to find the difference in knowledge before and after the intervention and a Mann-Whitney test to find the difference between media effectiveness in increasing knowledge. Results: The results show that both e-booklets (p-value = 0.000) and videos (p-value = 0.000) give a significant effect in increasing balanced nutrition knowledge levels. There is also no significant difference in the effectiveness of both media (p-value = 0.350). Conclusion: Balanced nutrition education using e-booklets and video proven to be effective in increasing nutrition knowledge in adolescents. Further research could be done by expanding the population and increase sample number.